UPAYA GURU FIQIH DALAM MENGEMBANGKAN KEMAMPUAN CRITICAL THINKING SISWA DI KELAS XI MADARASAH ALIYAH SWASTA BOLA KABUPATEN BUTON SELATAN - Nadya, Nadya; Madi; Basri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the critical thinking ability of eleventh-grade students in Fiqh subject and to describe the efforts of the Fiqh teacher in developing those abilities, including the supporting and inhibiting factors at Madrasah Aliyah Swasta Bola, South Buton Regency. This research employed a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews, and documentation study, then analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, and validated through source triangulation and technique triangulation. The findings reveal that students' critical thinking ability generally remains at a medium-to-low category, characterized by limitations in deeply analyzing Fiqh problems, constructing well-structured arguments, and independently evaluating legal opinions. The Fiqh teacher has made various developmental efforts through group discussions, HOTS-based questioning, and contextual case studies; however, the implementation has not been fully optimal due to time constraints, the dominance of lecture methods, significant heterogeneity in students' abilities, and the lack of varied learning resources. This study affirms that the gap between the efforts undertaken and the outcomes achieved requires more systematic, structured, and institutionally policy-based learning interventions. These findings contribute to the achievement of SDGs Goal 4 on inclusive and equitable quality education, particularly in promoting the equitable quality of critical thinking learning in private madrasah in remote island areas that have long been overlooked by educational research and national education policy.